2019
DOI: 10.12965/jer.1938422.211
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Movement Screen total score and physical performance in elite male collegiate soccer players

Abstract: The objectives of this study were to compare the differences in physical performance of elite male collegiate soccer players according to the Functional Movement Screen (FMS) total scores and to investigate the association between the FMS total score and physical performance. A total of 20 elite male collegiate soccer players (mean age, 19.6 ± 0.7 years; height, 173.4± 4.4 cm; body weight, 66.9± 7.3 kg; and body mass index, 22.0± 2.0 kg/m 2) participated in the present study. The subjects were divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
0
15
2
3
Order By: Relevance
“…Similar trend was also recorded in another studies ( Parchmann and McBride, 2011 ; Silva et al, 2017 ; Zalai et al, 2015 ) where no association between FMS total score and physical performance was obtained. However, our findings are in contrast to other studies where significant association between FMS total score and physical performance was recorded ( Lee et al, 2019 ; Lloyd et al, 2015 ). It should be noted that possible discrepancies between the studies may lie in the fact that different physical tests across these studies were performed and importantly, mean total score recorded in our study in each group was still above 15 points which indicate good results and reflect the reality in our age groups, whereas in this case, we were not able to divide players according to the low or high score as elsewhere ( Lee et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar trend was also recorded in another studies ( Parchmann and McBride, 2011 ; Silva et al, 2017 ; Zalai et al, 2015 ) where no association between FMS total score and physical performance was obtained. However, our findings are in contrast to other studies where significant association between FMS total score and physical performance was recorded ( Lee et al, 2019 ; Lloyd et al, 2015 ). It should be noted that possible discrepancies between the studies may lie in the fact that different physical tests across these studies were performed and importantly, mean total score recorded in our study in each group was still above 15 points which indicate good results and reflect the reality in our age groups, whereas in this case, we were not able to divide players according to the low or high score as elsewhere ( Lee et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, our findings are in contrast to other studies where significant association between FMS total score and physical performance was recorded ( Lee et al, 2019 ; Lloyd et al, 2015 ). It should be noted that possible discrepancies between the studies may lie in the fact that different physical tests across these studies were performed and importantly, mean total score recorded in our study in each group was still above 15 points which indicate good results and reflect the reality in our age groups, whereas in this case, we were not able to divide players according to the low or high score as elsewhere ( Lee et al, 2019 ). And probably due to the abovementioned situation and/or results may be that total score is less sensitive indicator of physical performance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Few studies have searched associations between FMS final score and performance variables in soccer athletes [16,18,24]. Lee et al [24] verified that FMS score could affect speed and agility of elite male collegiate soccer players and Lloyd et al [18] found moderate and high correlation between FMS total score and strength, power and agility in young soccer athletes. However, Silva et al [16] did not demons-trate a relation between FMS total score and performance variables, although the authors presented small associations with FMS individual scores in U-16 and U-19.…”
Section: Introductionmentioning
confidence: 99%